Metastatic prostate cancer with bone marrow infiltration mimicking multiple myeloma. Issue 2 (22nd December 2017) - Mathur, Pankaj; Alapat, Daisy; Kumar, Manoj; Thanendrarajan, Sharmilan
Key Clinical Message: Concomitant diagnosis of metastatic prostate cancer and a multiple myeloma in older male patients is challenging as both malignancies are usually associated with bone lesions. Exact knowledge, experience, and an interdisciplinary approach are required in order to differentiate between both malignancies and determine the exact treatment strategy. Abstract : Concomitant diagnosis of metastatic prostate cancer and a multiple myeloma in older male patients is challenging as both malignancies are usually associated with bone lesions. Exact knowledge, experience, and an interdisciplinary approach are required in order to differentiate between both malignancies and determine the exact treatment strategy.